# solve the following system by the addition method: 4x + 2y =-2; -4x -9y =23?

Please..really confused with this stuff.

### 8 Answers

- PhilomelLv 71 month agoFavorite Answer
4x-2y=-2

-4x-9y=23

add left sides; -7y=

add right sides; =21

divide y=21/-7=-3>>y=-3

4x-2(-3)=-2>> 4x-6=-2>>4x=-2+6=4>>x=1

check them in original equations.

4(1)-2(-3)=-2

-4(1) -9(-3)=23>>-4+27=23

Practice these, they are fun when you learn how.

- lenpol7Lv 71 month ago
Simultaneous Equations

Add the two equ'ns , this will eliminate 'x'.

-7y = 21

y = -3

When y = -3

4x + 2(-3) = -2

4x - 6 = -2

4x = 4

x = 1

Hence the answer in (x,y) form is ( 1, -3)

- la consoleLv 71 month ago
(1) : 4x + 2y = - 2

(2) : - 4x - 9y = 23

You calculate (1) + (2)

(4x + 2y) + (- 4x - 9y) = - 2 + 23

4x + 2y - 4x - 9y = 21

- 7y = 21

→ y = - 3

Recall (1) : 4x + 2y = - 2

4x = - 2 - 2y → we've just seen that: y = - 3

4x = - 2 + 6

4x = 4

→ x = 1

---------------------------------------------------------------------------------------------------------------------------------------

- PhilipLv 61 month ago
4x + 2y = -2...(1).;

-4x - 9y = 23...(2),;

[(1)+(2)] ---> -7y = 21, ie., y = -3. Then (1) ---> x = (1/4)(-2-2y) = -(1/2)(y+1) = 1.

- How do you think about the answers? You can sign in to vote the answer.
- Engr. RonaldLv 71 month ago
4x + 2y = - 2 Add eq1 and eq2

-4x - 9y = 23

----------------------

-7y = 21

y = -3

solving for x from eq1 by plugging in y = - 3.

4x + 2y = - 2

4x + 2(-3) = - 2

4x - 6 = - 2

4x = - 2 + 6

4x = 4

x = 1

The x and y values are: (1,- 3)............ Answer//

- Iggy RockoLv 71 month ago
4x + 2y = -2

-4x - 9y = 23

----------------

......-7y = 21

y = -3

4x + 2(-3) = -2

4x - 6 = -2

4x = 4

x = 1